Search for scalar leptons in e+e- collisions at √s = 189 GeV - Dova, María Teresa (1999)
We report the result of a search for scalar leptons in e+e- collisions at 189 GeV centre-of-mass energy at LEP. No evidence for such particles is found in a data sample of 176 pb-1. Improved upper limits are set on the production cross sections for these new particles. New exclusion contours in the parameter space of the Minimal Supersymmetric Standard Model are derived, as well as new lower limits on the masses of these supersymmetric particles. Under the assumptions of common gaugino and scalar masses at the GUT scale, we set an absolute lower limit on the mass of the lightest scalar electron of 65.5 GeV.